18F-FDG Superscan Caused by Extensive Bone Marrow Involvement in Hemophagocytic Lymphohistiocytosis. (August 2017) - Law, W. Phillip; Emmett, Shannon; Jackson, Peter
Abstract : Abstract: An 82-year-old woman who initially presented with pulmonary infection had persistent pancytopenia, which presented a diagnostic dilemma requiring multiple bone marrow biopsies for eventual diagnosis of hemophagocytic lymphohistiocytosis. This case highlights the utility of FDG PET in ( a ) focusing attention on the bone marrow and reticuloendothelial system as the primary site of pathology and ( b ) excluding underlying malignancy and infection in this rare but potentially fatal hyperinflammatory condition caused by a highly stimulated but ineffective immune response.